1980
DOI: 10.1016/s0022-5347(17)55628-1
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Bladder

Abstract: We present 2 cases of carcinosarcoma of the bladder. These tumors are considered as true admixtures of epithelial and mesenchymal neoplastic cells rather than 2 separate neoplasms that touch or marginally invade each other. Although the etiology of this tumor is unclear it tends to be aggressive and probably requires an early radical operation with adjuvant radiotherapy and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…74,79 Sarcomatoid carcinoma of the urinary bladder predominantly affects older adults and the elderly, with a predilection for male patients, and it has been reported in those with a history of radiation or cyclophosphamide therapy. 6,33,37,46,50,57,61 It tends to present at an advanced stage and is associated with a poor prognosis.Although pathologists have long recognized sarcomatoid carcinoma of the urinary bladder, 23,56 agreement on its proper classification and important findings clarifying its origins 4,12,63 are relatively recent developments. In this study, we discuss the classification terminology and clinical features of sarcomatoid carcinoma, and review its pathologic characteristics, including its morphology, immunohistochemical and ultrastructural profiles, and other entities from which it must be distinguished.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…74,79 Sarcomatoid carcinoma of the urinary bladder predominantly affects older adults and the elderly, with a predilection for male patients, and it has been reported in those with a history of radiation or cyclophosphamide therapy. 6,33,37,46,50,57,61 It tends to present at an advanced stage and is associated with a poor prognosis.Although pathologists have long recognized sarcomatoid carcinoma of the urinary bladder, 23,56 agreement on its proper classification and important findings clarifying its origins 4,12,63 are relatively recent developments. In this study, we discuss the classification terminology and clinical features of sarcomatoid carcinoma, and review its pathologic characteristics, including its morphology, immunohistochemical and ultrastructural profiles, and other entities from which it must be distinguished.…”
mentioning
confidence: 99%
“…74,79 Sarcomatoid carcinoma of the urinary bladder predominantly affects older adults and the elderly, with a predilection for male patients, and it has been reported in those with a history of radiation or cyclophosphamide therapy. 6,33,37,46,50,57,61 It tends to present at an advanced stage and is associated with a poor prognosis.…”
mentioning
confidence: 99%
“…Approximately 25 cases of signet ring cell carcinoma have been described, while only about 9 cases of mesonephric adenocarcinoma have been documented so far. Adenocarcinoma can exist in a pure form or as part of a mixed tumour with other epithelial elements such as transitional or squamous or as part of a carcinosarcoma (Schoborg et al, 1980;Smith et al, 1983). It is the most common malignant tumour occurring in an exstrophied bladder (Abeshouse, 1943) and more frequently seen in schistosomiasis-infested bladders (Makar, 1962).…”
mentioning
confidence: 99%
“…To observe the clinical features of spindle and giant cell carci noma and related tumors, 28 cases, consisting of 25 cases reported after 1970 [Brinton et al, 1970;Fujita et al, 1972;Floltz et al, 1972;Delides, 1972;Ostroffet al, 1973;Patterson and Dale, 1976;Kato et al, 1977;Kishi et al, 1977;Johansen et al, 1979;Schoborg et al, 1980;Chasko et al, 1980;Ando et al, 1981;Duong et al, 1981;Uyama and Moriwaki, 1981] and our 3 cases, were summarized. The mean age was 61.5 years (27-82 years).…”
Section: Discussionmentioning
confidence: 99%
“…The maleifemale ratio was 2.5 (20:8). 3 cases had histories of previous radiotherapy [Fujita et al, 1972;Schoborg et al, 1980] and 1 case had a history of prolonged administration of cyclophosphamide [Chasko et al, 1980]. These authors suggested the etiological significance of previous radiother apy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%